INVESTMENT ANALYSIS OF TUPKIES’ INVESTMENT PROPOSAL - Pajung, Adry Geraldo (Jurnal Pijar, 2023)
Tupkies is a small and medium-sized enterprise (SME) operating in the food and beverages industry, specifically as a cookies shop. The company aims to expand its business from an existing online store to establish a physical retail outlet. To raise the necessary capital for this expansion, Tupkies has prepared an investment proposal targeted at potential investors. The proposal includes financial projections with the ultimate focus on Return on Investment (ROI) to attract investors to participate in the Tupkies project. This paper's objective is to re-evaluate Tupkies from the author's perspective as an investor, assessing whether it presents a worthwhile investment opportunity or not. The analysis process encompasses several stages, commencing with an overview of the company and its investment proposal. Subsequently, financial projections are scrutinized, followed by a comprehensive feasibility analysis, business assessment, and concluding with a risk assessment conducted through scenario analysis. Through this examination, the paper seeks to determine Tupkies' true potential and ascertain its attractiveness as an investment prospect from the author's point of view. By applying rigorous financial tools and analysis, this study provides insights into Tupkies' viability and risk exposure, ultimately guiding the author's decision on whether to invest in the Tupkies project or explore other investment opportunities.